A New Coelurosaurian Theropod from the La Buitrera Fossil Locality of Río Negro, Argentina - Makovicky, Peter J. (2012)
A new coelurosaurian theropod, Alnashetri cerropoliciensis, is reported here based on articulated hind limbs of a single individual discovered at the locality of La Buitrera (Candeleros Formation, Cenomanian–Turonian), Río Negro Province, Argentina. The new taxon differs from other coelurosaurs in the possession of a low ridge that separates the rostral tibial surface from the outer face of the lateral malleolus, and which extends proximally beyond the tip of the ascending process of the astragalus, and in the possession of ventral notches on the hemicondyles of the distal articulations on pedal phalanges III-1 and III-2. Alnashetri is easily distinguished from the dromaeosaurid Buitreraptor, the only other known small theropod from La Buitrera. Phylogenetic analysis supports alvarezsauroid affinities. The evidence supporting this relationship comes from the detailed anatomy of the ankle, however, and this concentration of character support within a single anatomical region may bias our results. If our proposed phylogenetic placement is accurate, Alnashetri antedates all other Argentinian alvarezsaurids and indicates that alvarezsaurids were present in the Neuquén Basin throughout the entire Late Cretaceous.